Evaluation of HansBridge software for translation of web pages from English to Chinese. - Koh, Bee Yen. (2008)
Machine Translation, or MT, however imperfect it may be, is an actuality today. With the unprecedented exponential growth of the World Wide Web, MT has gained an increasingly important role in information exchange in today's borderless global economy. More and more vendors are offering machine translation services to the general web users. However, the use of MT systems for producing translations as good as those done by human translators has been disappointing in the past, even in domainspecific applications. The use of MT will only be fruitful in environments that can fully exploit the strong points. Thus, before we can safely assign the task of translating web pages to a MT system, it is important for us to see the product in a proper perspective, to be aware of its strengths and weaknesses.